How breeding of Brazilian soybean cultivars modified morphophysiological attributes of plants? - Umburanas, Renan Caldas (2019)
The average Brazilian soybean yield increased considerably from the beginning of the green revolution to the present day. Among the factors that contributed to the yield increase are the new technologies and agricultural practices, as well as the genetic gain provided by plant breeding. While soybean yield increased through breeding efforts, morphophysiological changes in Brazilian cultivars that contributed to yield increase are largely unknown. The objective of this study was to understand how morphophysiological changes increased yield in soybean cultivars grown in the last 50 years in Southern Brazil. The study was divided into three chapters: the first chapter refers to the experiment conducted in the field to evaluate yield and its components in 26 cultivars; the second chapter refers to the experiment conducted in pots to evaluate the roots of 25 cultivars; and the third chapter refers to two experiments in which attributes of energy conversion efficiency, foliar aging and plant response to elevated CO2 in the atmosphere were evaluated in 5 cultivars. The results showed that the yield increase was consistent throughout the years of cultivar release and the rate of increase was 46 kg ha-1 year-1. Among the yield components contributing to this increase we include the increase of biomass per area and harvest index, which therefore provide more seeds per area, due to a greater number of pods and seeds per pod. The lodging resistance improved during the year of cultivar release. For further increases in soybean yield, potential targets in future cultivars are increasing leaf nitrogen content at the R5 growth stage and the biological nitrogen fixation. Mean root diameter was reduced throughout the years of cultivar release, while the attributes total length, volume, projected area and root length were not consistently modified. The evaluated soybean cultivars presented consistent changes under elevated CO2 atmosphere [720 ppm]: the leaf chlorophyll content was reduced, the specific leaf area reduced, and the stem biomass partition increased. The old leaves presented less assimilation, less stomatal conductance, and lower leaf temperature in relation to the new leaves. However, they presented higher concentration of intercellular CO2, higher specific leaf area and chlorophyll content. The results obtained in this study will certainly contribute to strategies in breeding programs in the development of soybean cultivars that are more productive in the future. The results obtained identified morphophysiological changes in a selection of soybean cultivars grown in Southern Brazil.